Development of Student Worksheets for Inquiry Model in Differentiated Learning to Improve Students' Critical Thinking - Aeti, Siti; Sumarno, Sumarno; Dwijayanti, Ida (Journal of Innovation and Research in Primary Education, 2025)
Conditions of grade V students of SDN Kubangjati 02 have an impact on the low scores of computer-based national assessments and education report cards. To overcome this problem, a learning model was developed to stimulate students' critical thinking process by using Student Worksheets (LKPD) in differentiated learning through the inquiry learning model. This study aims to analyze the effectiveness of the LKS device in differentiated learning through the inquiry learning model to improve students' critical thinking processes and abilities. The type of research used is development research. The data collection techniques used are tests, interviews, questionnaires, and documentation. The data analysis techniques used are normality tests, homogeneity tests, paired sample t-tests, and N-Gain tests. The results of the practicality test of the developed LKS student response questionnaire were stated to be practical by students with an average score of 91.4 and were categorized as very good. The output results of "Paired Samples Correlations" obtained a Sig. value. of 0.000 < 0.05, so there is a difference in the average learning outcomes of the pretest and posttest, which means that the use of student worksheets with inquiry in differentiated learning can improve the critical thinking process of elementary school students. Conclusion: (1) Student worksheets with the inquiry learning model have been proven to be able to build student enthusiasm in differentiation learning, (2) Student worksheets with the inquiry learning model have been proven to be able to improve students' critical thinking processes in differentiation learning, and (3) Student worksheets with the inquiry learning model have been proven to be able to improve students' critical thinking skills in differentiation learning.